PENATALAKSANAAN NEKROSIS PULPA DISERTAI LESI PERIAPIKAL PADA GIGI 47 - Rezy Kurnia; Deli Mona (Andalas Dental Journal, 2018)
Root canal treatment is divided into 3 stages, namely the biomechanical preparation stage of the root canal, the sterilization and disinfection stage of the root canal, and the root canal filling stage. The success of root canal filling depends on the state of asepsis, thorough cleaning of the pulp tissue, biomechanical preparation, and hermetic root canal filling. After root canal treatment, teeth require different treatment than vital teeth, due to reduced moisture in these teeth and a reduction in dentin during the root canal preparation process, which affects the remaining hard tissue structure of the teeth. There are several types of restorations that can be used after root canal treatment. Post-root canal restoration treatment using composite resin materials can be made directly or indirectly, the technique must be able to strengthen the remaining hard tissue structure of the teeth and restore tooth function. If some of the teeth are missing but still have sufficient thickness of the dentin enamel structure and the patient wants a tooth-colored restoration, indirect composite onlay may be an option.